Attitudes Toward Unhealthy Relationship Behaviors and Boundary-Setting: Variation Among High School Students - Moschella-Smith, Elizabeth A. (Journal of interpersonal violence, 2025)
Teen dating violence (TDV) is common during adolescence and has lasting negative impacts on those who experience it. Yet, there is limited research exploring how well teens recognize unhealthy behaviors and communicate boundaries, both crucial aspects in preventing TDV. This study aimed to investigate how demographic characteristics (i.e., gender, age, sexual identity, and race/ethnicity) relate to adolescents’ abilities to recognize unhealthy relationships and willingness to communicate boundaries. Participants (N = 873) completed online surveys during school hours on demographic characteristics (e.g., gender), recognition of unhealthy relationship behaviors, communicating boundaries, and navigating breakups. We found that girls, participants who identify as a sexual minority (e.g., lesbian), and White participants demonstrated significantly higher recognition of controlling behaviors compared to boys and their heterosexual and non-White counterparts, respectively, but there was no significant difference in identifying abusive behaviors such as shouting, yelling, and insulting a partner. Older participants (i.e., ages 16–18) were significantly more likely to recognize controlling and abusive behaviors as unhealthy compared to younger participants (i.e., 13–15). Further, we found that girls and older participants were significantly more willing to communicate boundaries in relationships than boys and their younger counterparts. Our findings align with prior research emphasizing the necessity for prevention strategies that raise awareness of controlling behaviors that can escalate to more severe forms of TDV and equip adolescents with the means to establish and communicate personal boundaries.